Production and Seed Chemical Composition of Three Edamame Soybean Cultivars in The Medium Plains of Aceh, Indonesia - Amin, Muhammad; Syafruddin, Syafruddin; Sufardi, Sufardi; Muyassir, Muyassir (AGRIVITA Journal of Agricultural Science, 2025)
Increasing soybean productivity in Indonesia remains a challenge due to infertile soil and a lack of research on the most suitable varieties of soybeans. One strategy to address consistently low yields is the introduction of edamame cultivars, which are native to the subtropics. The purpose of this study is to examine the adaptation, production, and quality of edamame soybean products in the Aceh Medium Plain, Indonesia. Three edamame soybean cultivars, namely Riocos 305, Biomax 1, and Biomax 2, have been tested at an elevation of 612 m above sea level in the soil of the Andisols order. The three cultivars exhibited distinct responses in terms of growth, production, and seed quality. Biomax 1 showed the highest productivity, with a seed yield of 2.10 t/ha, compared to 0.95 t/ha for Riocos 305 and 0.64 t/ha for Biomax 2. While the three cultivars exhibited similar seed quality, the nutrient composition differed between mature seeds and dried seeds.